Microbiological Isolates and Antibiotic Susceptibilities in Cases of Posttraumatic Endophthalmitis: A 15-Year Review - Chunhong Liu; Jian Ji; Zhujian Wang; Huiwen Chen; Wenjun Cao; Xinghuai Sun (Journal of Ophthalmology)
Purpose. The objective of this study was to evaluate the microbiological spectrum and antibiotic susceptibilities of isolates in posttraumatic endophthalmitis over a 15-year period. Methods. A retrospective study of 3,163 posttraumatic endophthalmitis cases was conducted between July 2004 and July 2019. The outcome measures included the microbiological spectrum and antibiotic susceptibilities. Chi-squared tests were conducted to detect trends in changes in antibiotic sensitivity over the 15-year period. P values of <0.05 were considered statistically significant. Results. Of the 3,163 cases of posttraumatic endophthalmitis, 1,003 culture-positive isolates were identified. Among these, there were 848 (84.5%) Gram-positive isolates, 109 (10.9%) Gram-negative isolates, and 46 (4.6%) fungal isolates. The most common isolates were Staphylococcal species. There was a significant increase in the percentage of fungal isolates over the 15-year period (P=0.02). Gram-positive organisms showed the greatest level of susceptibility to vancomycin (99.6%). The susceptibilities of the 109 Gram-negative isolated organisms were as follows: levofloxacin (95.8%), meropenem (95.7%), ciprofloxacin (93.5%), tobramycin (90.8%), imipenem (88.9%), trimethoprim-sulfamethoxazole (TMP-SMX) (87.7%), ertapenem (80%), and ceftazidime (79.1%). The susceptibility of Gram-positive organisms to several antibiotics, including levofloxacin (P=0.004), ciprofloxacin (P<0.001), and chloramphenicol (P=0.001) decreased over time, whereas the susceptibility to TMP-SMX increased over time (P<0.001). The susceptibility of Gram-negative bacilli to ceftazidime decreased over time (P=0.03). Conclusions. Over the 15-year study period, most isolates were Gram-positive cocci, especially coagulase-negative staphylococci (CNS). Vancomycin seemed to be the most effective antibiotic for Gram-positive bacteria. Gram-negative bacteria appeared to be most susceptible to fluoroquinolones. A number of antibiotics showed an increasing trend of microbial resistance.